Identifikasi Sebaran Tanaman Pangan Kabupaten Kupang Menggunakan Citra Satelit Landsat 8 - Raymond Elias Mauboy; Sri Yulianto Joko Prasetyo; Charitas Fibriani (Indonesian Journal of Computing and Modeling, 2019)
Hunger is a big problem for the community due to lack of food in a region, this problem often occurs in areas that have a low level of agricultural land management, areas in East Nusa Tenggara often experience famine almost every year, agricultural areas The government should be able to explain it well so that it can find out which areas are agricultural areas, settlements and forest areas so that the process of managing agricultural land has been known by the government and the community, this is a problem that often occurs in the East Nusa Tenggara region , the lack of agricultural distribution areas in the East Nusa Tenggar area, especially the Kupang Regency area, led researchers to conduct research on the Identification of Kupang Regency Food Crop Distribution Using Landsat 8 Satellite Imagery aimed at more agricultural distribution areas. this is known to the government and the community so that it can reduce the rate of hunger in Kupang district